antioxidant activity Uji aktivitas antioksidan ekstrak daun karet kebo (Ficus elastica) dengan menggunakan metode maserasi bertingkat - Yani, Indah Ahmad; Suhaenah, Asriani; Aminah, Aminah (PHARMACY UMI JOURNAL SYSTEM, 2024)
Kebo rubber (Ficus elastica) is one type of plant in Indonesia as a medicine to lower blood pressure, reduce cholesterol, stroke and reduce joint pain. In addition, Kebo rubber (Ficus elastica) leaves are one of the ficus species that are thought to be rich in polyphenolic compounds so that they can act as antioxidants. Antioxidants are compounds that can be used to counteract free radicals. Food fiber and antioxidants are two types of components that are very beneficial in improving health and being able to prevent various diseases. This study aims to analyze the antioxidant activity of rubber kebo (Ficus elastica) leaf extract using the DPPH method. The maceration process uses 3 different types of solvent, namely n-hexane (non-polae), ethyl acetate was measured at 510 nm wavelength with quercetin as the standard comparator. The measurement result for n-hexan extract obtained IC50 of 531,90 µg/mL, ethyl acetat obtained IC50 of 188,06 µg/mL, and for ethanol extract obtained IC50 of 874,73 µg/mL.